Resistance monitoring of larvae treated with Bt cotton and pesticides in Helicoverpa armigera (Lepidoptera: Noctuidae). (3rd July 2017) - Pan, Lidong; Shi, Ming; Chen, Jin; Wei, Qi; Gao, Congfen
Abstract: Transgenic Bt cotton was first introduced into Qiuxian County (Hebei, China) in order to control the cotton bollworm, Helicoverpa armigera, in 1998. Owing to the high selection pressures in this region, monitoring of Bt resistance in H. armigera is critical to verify the efficacy of transgenic cotton and construct the new management strategy. The F2 screen was conducted to detect the resistance allele frequency in the field population of H. armigera in Qiuxian County from 2010 to 2012. The annual values were 0.0389 (95% CI: 0.0064–0.0714), 0.0372 (95% CI: 0.0036–0.0708) and 0.0781 (95% CI: 0.0318–0.1244), respectively. In order to test the optional insecticides to control H. armigera, through leaf-dip bioassay, the resistance of field population from Qiuxian to 6 insecticides were detected. The results showed Qiuxian population was kept high resistance to cyhalothrin (Resistance Ratio = 61.8–95.2) and to beta-cypermethrin (Resistance Ratio = 50.9–82.3), low to moderate resistance to phoxim (Resistance Ratio = 9.1–23.7), and susceptibility to emamectin benzoate, abamectin and spinosad. Emamectin benzoate, abamectin and spinosad are the alternative options for controlling H. armigera in Qiuxian County, if the efficacy of Bt cotton is compromised by Bt resistance in the field.